An experience with covered transjugular intrahepatic portosystemic shunt for refractory ascites from western India - Deepak N. Amarapurkar (Annals of Hepatology, 2006)
Background: In refractory ascites/hydrothorax (RA), uncovered transjugular intrahepatic portosystemic shunt (TIPS) is shown to be superior to large-volume therapeutic paracentesis (LVP) for long-term control of ascites, but at a cost of increased risk of hepatic encephalopathy (HE). Use of covered TIPS has shown to improve shunt patency rate over uncovered TIPS. This retrospective analysis was performed on patients with RA to assess efficacy of TIPS, both covered and uncovered. Methods: Over 10-year period, patients with RA, patients either required LVP at least 2 times in a month, or were intolerant to LVP, or were unwilling to undergo further LVP, were treated with TIPS (Group-A = 12 patients with uncovered TIPS {Wallstent = 10, Memotherm = 1, SMART = 1}, age = 56.1 ± 4.5 years, male: female = 5:1; Group-B = 11 patients with e-PTFE-covered TIPS {Viatorr = 11}, age = 55.8 ± 5.2 years, male: female = 8:3). They were followed-up with clinical and ultrasonography/Doppler examination every monthly for 3 months and every 3 monthly thereafter (mean = 9.6 ± 4.2 months). Clinical success (disappearance of ascites at 1-month), technical success (post-TIPS reduction of portosystemic pressure gradient PPG < 12 mmHg), appearance of encephalopathy, TIPS-dysfunction (> 50% reduction in flow-velocity, > 50% shunt stenosis or increase in PPG > 12 mmHg in presence of symptoms) and mortality were noted. Data were analyzed using chi-square test and t test. Results: Baseline clinical and biochemical characteristics were similar in both groups. TIPS placement was possible in 11/12 group-A and 11/ 11 group-B patients. Fall in PPG after TIPS was similar in both groups. One patient in group-A was lost follow-up after the procedure. On comparison of group-A and group-B, clinical success (63.3% and 81.8%), technical success (90.9% and 100%), occurrence of HE (60% and 54.4%) and mortality at 1-year (70% and 63.3%) were not significantly different. TIPS-dysfunction requiring re-intervention was significantly more common in group-A (50%) than group-B (0%). Conclusions: Covered TIPS was superior to uncovered TIPS, because of less TIPS-dysfunction without increasing chances of HE; but failed to offer any survival advantage.